5 - Restore, Reform but do not Transform: The Gender Politics of Higher Education in Africa: Amina Mama - Amina Mama (Journal of Higher Education in Africa, 2003)
This paper uses gender analysis to reflect on the emergence and development of higher education in Africa. The available statistical picture indicates that despite the absence of formal exclusions, women’s entry into higher educational institu- tions—as students and as employees—has remained slow and uneven, suggesting the need to look beyond the numbers. The overall pattern of exclusion and marginalization is true for both administrative and academic tracks but is at its most extreme for senior academic and research positions. The persistence of extreme gender inequality is most easily and often attributed to external social and familial factors. Here, however, it is argued that there is sufficient evidence to suggest that, despite institutional and managerial claims of administrative neutrality, the institu- tional and intellectual cultures of African institutions are, in fact, permeated with sexual and gender dynamics.